POLA KEJADIAN PNEUMONIA BALITA: ASPEK GIZI DAN RIWAYAT PENYAKIT - Nursiah, Andi; Muhsinin, Muhsinin; Suyati, Suyati; Jehaman, Tonsisius (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Pneumonia is one of the deadliest infectious diseases and the leading cause of death in children worldwide. Paal V Health Center is one of the health centers with the highest pneumonia cases in Jambi City. The purpose of the study was to determine the relationship of nutritional aspects and disease history to the incidence of pneumonia in toddlers. The research design used in this study was cross sectional. The study was conducted at the Paal V Health Center in January 2024. The population consisted of 87 toddlers (aged 0-59 months) who experienced severe pneumonia and mild pneumonia at Puskesmas Paal V. The sample size was 87 respondents. The sampling technique used in this study was total sampling. Data were analyzed univariately and bivariately. The results showed a relationship between nutritional status (p value: 0.000) and history of ARI (p value: 0.003) to the level of pneumonia in toddlers. It is recommended that mothers of toddlers be more active and careful in seeking information about the right food and of course can meet the nutritional status of toddlers without waiting for counseling from health workers about good nutritional status. In addition, mothers are expected to pay attention to food intake for toddlers, so that the nutritional status of toddlers becomes good and can prevent the occurrence of infectious diseases in toddlers, especially pneumonia.Keywords: Toddlers, Nutrition, Medical History.